New type NP-CSMA of adaptive multi-priority control WSN protocol analysis. (5th February 2021) - Han, Zejun; Ding, Hongwei; Yue, Kun; Bao, Liyong; Yang, Zhijun
Wireless sensor networks (WSN) uses a large number of cheap micro sensor nodes, which can be used to perceive and deal with the information that the transmission network covers the object in the geographic area, so it is very popular among people. P-CSMA access to WSN can control the system and reduce energy consumption, but the overall effect is general and the practicability is common. In this paper, a three-clock non-persistent P-CSMA (NP-CSMA) based on variable collision length is proposed to improve system throughput. By dividing the successful packet transmission time (1 + a ), the collision packet transmission time ( b + a ), the free packet sending time a, the average cycle method is used to find out the important parameters of the system, such as throughput, collision rate and idle rate, striving to minimise the system energy consumption, effectively extending the life cycle of nodes and reducing costs. Finally, simulation experiments are validated the validity of the agreement, comparing with other protocols to verify the superiority of this agreement.